Konsep Dasar Evaluasi Pembelajaran pada lembaga pendidikan PAUD (Pendidikan Anak Usia Dini) : Penelitian - Dahliana Usni Fitriani Lubis; Annida Khairunnisa; Febby Elya Tantri; Tari Dwi Gustiayu; Ampun Bantali (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Learning evaluation plays a crucial role in early childhood education because it helps teachers understand child development and the effectiveness of learning activities. This study aims to examine early childhood learning evaluation, encompassing basic concepts, objectives, principles, types, and evaluation methods. The study employed a qualitative descriptive approach through a literature review, reviewing various relevant sources. The study's findings indicate that early childhood learning evaluation needs to be conducted continuously, taking into account both the child's learning process and outcomes. Various techniques, such as observation, portfolios, interviews, and assessment of work, are used to obtain a picture of child development. Appropriately implemented evaluation can serve as a basis for future learning planning and support optimal child development.